2021
DOI: 10.1002/2688-8319.12032
|View full text |Cite
|
Sign up to set email alerts
|

Training future generations to deliver evidence‐based conservation and ecosystem management

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Therefore, the use of existing non-English-language science is not a panacea. Generating more local evidence, based on robust study designs, and publishing it in any language should be further encouraged and supported globally, but especially in those evidence-poor regions, for example, through the distribution of free teaching materials to facilitate the testing of conservation interventions [ 28 ]. Although not included in this study, non-English-language grey literature could be another potentially important source of evidence [ 29 ]; whether and how non-English-language grey literature might fill gaps in English-language evidence still remains to be tested (also see Limitations in Materials and methods for other limitations).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of existing non-English-language science is not a panacea. Generating more local evidence, based on robust study designs, and publishing it in any language should be further encouraged and supported globally, but especially in those evidence-poor regions, for example, through the distribution of free teaching materials to facilitate the testing of conservation interventions [ 28 ]. Although not included in this study, non-English-language grey literature could be another potentially important source of evidence [ 29 ]; whether and how non-English-language grey literature might fill gaps in English-language evidence still remains to be tested (also see Limitations in Materials and methods for other limitations).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a survey of environmental policy makers in Canada revealed that they were aware of the value of systematic reviews and would use them preferentially over other forms of evidence if they were available for a given issue or topic (Thomas-Walters et al 2021). In addition specialized training of practitioners and managers has been proposed as a solution to decrease information overload and mitigate time limitations (Cook et al 2013;Downey et al 2021), especially for WBS that is technical in nature and prone to using jargon (e.g., conservation genomics). Further, Downey et al ( 2021) created a database of online teaching materials stored on the Applied Ecology Resources website, which include development courses aimed at improving skills related to appraisal and increased use of WBS in decision making and NRM.…”
Section: Discussionmentioning
confidence: 99%
“…Natural resources management (NRM) also involves managing habitat and the people who engage and interact with fish, wildlife, and ecosystems such as hunters, anglers, and other increasingly diversified actors (e.g., industry, farmers, private landowners, conservation organizations, rights holders, non-profit organizations (ENGOs), environmental consultants, and community groups). Further, these actors may have high expectations for involvement in programs and decisions (Decker et al 2012). Salafsky et al (2019) define evidence as information that contributes to the assessment of hypotheses related to a question of interest in the form of basic data, primary studies, syntheses, decision support systems, and/or theory.…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners have also reported a lack of skills in evaluating evidence and critical thinking (Downey et al 2021). Ockendon et al (2021) identifies barriers to testing, especially the challenge of identifying suitable experimental designs, and offers guidance on overcoming them.…”
Section: Introductionmentioning
confidence: 99%
“…Using these as the basis of a 'toolkit' for practitioners to use evidence-based conservation, we can identify where there are gaps in our knowledge on how to find, test, and interpret the evidence. In addition, Downey et al (2021) identified five key elements required in the teaching of evidence-based conservation: Ask, Access, Appraise, Apply, Audit. The first step, Ask (identifying the problem and formulating a focused question), is the target of this paper.…”
Section: Introductionmentioning
confidence: 99%